PREDIKSI EROSI DAN SEDIMENTASI PADA BERBAGAI PENGGUNAAN LAHAN DI SUB DAS MASANG BAGIAN HULU DI KABUPATEN AGAM - Aprisal Aprisal (Jurnal Solum, 2011)
Erosion and sedimentation prediction in sub-watershed Masang was conducted to predict amount of soil eroded and sedimented from several land use in the location, and to find out  alternative land use that can suppress erosion to be equal to or less than tolerated erosion as well.  Methods employed to do this research were 1) analysis of basic data (topography map, land use map, and secondary data such as rainfall data from the nearest meteorology station), 2) soil survey and identification to field, 3) soil analyses at laboratorium, and 4) data analyses using USLE erosion model and sediment delivery ratio (SDR).  The results showed that amount of soil eroded from all land use except from forest was higher than tolerated erosion.  Among the types of land use were mixed garden, housing, plantation, and bush.  Higher erosion than tolerated erosion was probably due to low plant density, big percentage of uncover land, therefore, raindrops became easier to hit soil and then disperse the aggregates.  As a consequence, erosion and sedimentation became bigger.  Soil eroded could be minimized into the same or less than tolerated erosion by implementing conservation agroecotechnology by reducing crop coefficient value (into 0.001) through increasing plant density and changing bush land into garden or plantation.  For housing area, the area should be planted by perennial crops, should be provided by terraces to ditches to pass runoff.  Soil sedimentl was calculated to be higher from garden and bush, but by implementing agroecotechnology conservation sediment can be controlled.Keywords: erosion, sedimentation, watershed